The dark earl [large type] - Henley, Virginia (Thorndike Press large print basic series., 2012)
It's love at first sight for Lady Harriet Hamilton - with Thomas Anson's ancestral home. His father, the Earl of Lichfield, has gambled away the family's honor, and it's cost them everything. The estate sale is shameful enough for Thomas without some little brat sneaking around. When they meet again years later, Harry is outspoken, audacious, and now, quite a beauty. But Thomas is committed to restoring the family holdings, not chasing after a wife.